INTEGRATED DESIGN OF ALTERNATIVE ENERGY OPTIONS - A MULTICRITERIA APPROACH - Heracles Polatidis; Dias Haralambopoulos (European Regional Science Association (ERSA), 2005)
Energy planning has come a long way during the 20th century from an intuitive approach to a full-scale discipline, incorporating technological and economic dimensions. The latter include both the micro- and the macro- level, whereas the technological framework covers energy, technology, thermodynamics and thermo-economic approaches. It is only during the last two decades that the environmental aspects of energy conversion has started to assume the gravity that it should have been assigned perhaps from the start, with the deterioration of the environment, e.g. acid rain, urban pollution, global warming, etc. and the depletion of resources becoming issues of outmost importance. The emergence of the renewable energy technologies as a reliable substitute of conventional fossil fuels gave promises that were only partially fulfilled as they never assumed the role that society had entrusted on them in the beginning. The alternative energy options, both on the technological and the resource level, revealed the complex nature of energy planning, where energy production and conversion should be addressed in tandem with energy demand and consumption and the particular preferences of the individuals. In both cases the spatial elements should be carefully analyzed and taken into consideration. Today's energy planning asks for a complex approach which must includes the technological, economic, environmental and social design, accounting for the multitude of facets that interweave in the analysis and successful implementation of energy policies and projects. The aforementioned four dimensions must in turn be decomposed in a number of attributes in order for a quantitative and qualitative estimation to be realized. For the identification of an appropriate solution, a multi-criteria analysis seems to be the logical framework since it allows for a multitude of elements to be incorporated, and at the same time it can include a variety of stakeholders, with conflicting perhaps interests. In this paper we present the new approach for energy planning with the technological, economic, environmental and social design dimensions integrated in a new platform together with the necessary decomposition analysis. The whole new framework is presented via theoretical and practical examples and will hopefully pave the way towards a new under transition, energy future.
Keywords: 330